Roles of Library Research Institutions in Disseminating Research Publications: A Bibliometric Study - Tupan,; Rachmawati, Rulina (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2022)
This study seeks to ascertain the distribution of research publications concerning the roles of libraries and librarians in research institutions listed in the Scopus database. A literature search uncovered 1637 articles on the subject. R-Bibliometrix (Biblioshiny) software was used to evaluate these publications in considerable detail. The findings indicated that Library Philosophy and Practice was the publication that published the most significant number of articles on the relevant themes, with Pandita R. being the most productive author. Scientometrics received the most citations (515), followed by The Journal of Academic Librarianship (410), College Research Libraries (399), and Library Management (317 times). The Journal of Academic Librarianship and Library Philosophy and Practice had the highest h-index scores, 9 and 7, respectively. The United States contributed the most to collaboration; of the 260 papers where 246 documents have collaborated across the country, and 14 papers collaborated with authors from several countries. The widely studied topics include libraries, medical libraries, library science, organization and management, librarian of biomedical research, scientific libraries, qualitative research, meta-analysis, systematic reviews, and Cochrane libraries